Objectifying Men: Gulliver’s Travels, Fantomina, and the Dildo in Eighteenth-Century Literature - Andrea K Gill (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2011)
Eighteenth-century literature is saturated with satires on the human body, especially the female body. This is most notable in the writings of men such as Jonathan Swift, Rochester (John Wilmot), and Samuel Pepys in which the authors depict the female body as being unclean and, in some cases, ugly or disproportionate. Women’s bodies were often objectified sexually as if currency and were used as social exchanges between men. Most notably, this occurs between the characters of The Country Wife. When the dildo was introduced to eighteenth-century England, women were able to take their sexuality into their own hands, literally, and men became fearful that women would no longer have need of them.